1989
DOI: 10.1002/j.1460-2075.1989.tb03523.x
|View full text |Cite
|
Sign up to set email alerts
|

Joining of linear plasmid DNA is reduced and error-prone in Bloom's syndrome cells.

Abstract: A linearized, replicating, shuttle vector plasmid, pZ189, was used to measure in vivo DNA joining ability of cells from patients with the cancer‐prone, immunodeficient, chromosome breakage disorder, Bloom's syndrome (BS). The BS cell lines we studied were reported to contain reduced in vitro activity of DNA ligase I. We assessed in vivo joining ability by transfecting linear plasmids with overlapping or blunt ends (produced by EcoRI or StuI) into BS and normal fibroblast or lymphoblast host cells and measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 26 publications
(22 reference statements)
4
21
1
Order By: Relevance
“…An assessment of stability was then made through electrophoretic comparison of the BamHI-HindIII and BamHI-BamHI fragments to the starting material. As previously observed, several rescued plasmids contained insertions of either genomic or plasmid DNA (27) and yielded aberrant restriction digestion patterns. The occurrence of these recombinants did not correlate with either repeat tract length or the presence of slipped structures (data not shown).…”
Section: Double-strand Break Assay Andsupporting
confidence: 75%
See 3 more Smart Citations
“…An assessment of stability was then made through electrophoretic comparison of the BamHI-HindIII and BamHI-BamHI fragments to the starting material. As previously observed, several rescued plasmids contained insertions of either genomic or plasmid DNA (27) and yielded aberrant restriction digestion patterns. The occurrence of these recombinants did not correlate with either repeat tract length or the presence of slipped structures (data not shown).…”
Section: Double-strand Break Assay Andsupporting
confidence: 75%
“…This is the first time this phenomenon has been observed for a DSB located within a repeat tract in primate cells. Similar double-strand break repair assays that have not concerned repeating sequences have also found deletions to be the most common result of improper DSB repair (27,32). It has been proposed that this bias toward deletions is likely a result of fraying/ unwinding at the two free ends of the double-strand break, thereby becoming suitable substrates for repair/recombination enzymes (33).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, Bloom's syndrome is a rare disorder in humans caused by mutations in the RecQ helicase BLM that results in a predisposition to cancers of all types (Hickson 2003). Evidence for a role of this helicase in DSB metabolism comes from its involvement in homologous recombination-dependent repair of damaged replication forks (Wu and Hickson 2003) and from the fact that mending of dsDNA breaks in the absence of BLM results in defective products with large deletions (Runger and Kraemer 1989;Gaymes et al 2002). The ortholog of BLM in Drosophila is encoded by mus309 (Kusano et al 2001), a gene identified in a screen for hypersensitivity to chemical DNA-damaging agents such as nitrogen mustard, a mutagen that induces interstrand DNA crosslinks, and MMS (Boyd et al 1981).…”
Section: Discussionmentioning
confidence: 99%